3/2 5/x-3=x 9/2x-6

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

Algebra 

Jul 16th, 2015

Thank you for the opportunity to help you with your question!

Two solutions were found :

  1.  x =(-9-√521)/-22= 1.447
  2.  x =(-9+√521)/-22=-0.628

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation : 

  3/2+5/x-3-(x+9/2*x-6)=0 

Step by step solution :

Step  1  :

                 9x
Simplify   x  +  ——
                 2 

Rewriting the whole as an Equivalent Fraction :

 1.1  Adding a fraction to a whole 

Rewrite the whole as a fraction using   as the denominator :

          x     x • 2
     x =  —  =  —————
          1       2  

Equivalent fraction : The fraction thus generated looks different but has the same value as the whole 

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :

 1.2   Adding up the two equivalent fractions 
Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

 x • 2 + 9x     11x
 ——————————  =  ———
     2           2 

Equation at the end of step  1  :

    3 5      11x
  ((—+—)-3)-(———-6)  = 0 
    2 x       2 

Step  2  :

           11x     
Simplify   ———  -  6
            2      

Rewriting the whole as an Equivalent Fraction :

 2.1  Subtracting a whole from a fraction 

Rewrite the whole as a fraction using   as the denominator :

          6     6 • 2
     6 =  —  =  —————
          1       2  

Adding fractions that have a common denominator :

 2.2   Adding up the two equivalent fractions 

 11x - (6 • 2)     11x - 12
 —————————————  =  ————————
       2              2    

Equation at the end of step  2  :

    3    5           (11x - 12)
  ((— +  —) -  3) -  ——————————  = 0 
    2    x               2     

Step  3  :

           3     5
Simplify   —  +  —
           2     x

Calculating the Least Common Multiple :

 3.1   Find the Least Common Multiple 

  The left denominator is :   

  The right denominator is :   

 Number of times each prime factor
 appears in the factorization of:
 Prime 
 Factor 
 Left 
 Denominator 
 Right 
 Denominator 
 L.C.M = Max 
 {Left,Right} 
2101
 Product of all 
 Prime Factors 
212
 Number of times each Algebraic Factor
 appears in the factorization of:
 Algebraic 
 Factor 
 Left 
 Denominator 
 Right 
 Denominator 
 L.C.M = Max 
 {Left,Right} 
 x 011


  Least Common Multiple: 
  2x 

Calculating Multipliers :

 3.2   Calculate multipliers for the two fractions 


  Denote the Least Common Multiple by  L.C.M 
  Denote the Left Multiplier by  Left_M 
  Denote the Right Multiplier by  Right_M 
  Denote the Left Deniminator by  L_Deno 
  Denote the Right Multiplier by  R_Deno 

 Left_M = L.C.M / L_Deno = x

 Right_M = L.C.M / R_Deno = 2

Making Equivalent Fractions :

 3.3   Rewrite the two fractions into equivalent fractions

Two fractions are called equivalent if they have the same numeric value.

For example :  1/2   and  2/4  are equivalent,  y/(y+1)2  and  (y2+y)/(y+1)3 are equivalent as well. 

To calculate equivalent fraction , multiply the Numerator of each fraction, by its respectiveMultiplier.

   L. Mult. • L. Num.      3 • x
   ——————————————————  =   —————
         L.C.M              2x  

   R. Mult. • R. Num.      5 • 2
   ——————————————————  =   —————
         L.C.M              2x  

Adding fractions that have a common denominator :

 3.4   Adding up the two equivalent fractions 

 3 • x + 5 • 2     3x + 10
 —————————————  =  ———————
      2x             2x   

Equation at the end of step  3  :

   (3x + 10)          (11x - 12)
  (————————— -  3) -  ——————————  = 0 
      2x                  2     

Step  4  :

           3x+10     
Simplify   —————  -  3
            2x       

Rewriting the whole as an Equivalent Fraction :

 4.1  Subtracting a whole from a fraction 

Rewrite the whole as a fraction using  2x  as the denominator :

          3     3 • 2x
     3 =  —  =  ——————
          1       2x  

Adding fractions that have a common denominator :

 4.2   Adding up the two equivalent fractions 

 (3x+10) - (3 • 2x)     10 - 3x
 ——————————————————  =  ———————
         2x               2x   

Equation at the end of step  4  :

  (10 - 3x)    (11x - 12)
  ————————— -  ——————————  = 0 
     2x            2     

Step  5  :

           10-3x     11x-12
Simplify   —————  -  ——————
            2x         2   

Calculating the Least Common Multiple :

 5.1   Find the Least Common Multiple 

  The left denominator is :   2x 

  The right denominator is :   

 Number of times each prime factor
 appears in the factorization of:
 Prime 
 Factor 
 Left 
 Denominator 
 Right 
 Denominator 
 L.C.M = Max 
 {Left,Right} 
2111
 Product of all 
 Prime Factors 
222
 Number of times each Algebraic Factor
 appears in the factorization of:
 Algebraic 
 Factor 
 Left 
 Denominator 
 Right 
 Denominator 
 L.C.M = Max 
 {Left,Right} 
 x 101


  Least Common Multiple: 
  2x 

Calculating Multipliers :

 5.2   Calculate multipliers for the two fractions 


  Denote the Least Common Multiple by  L.C.M 
  Denote the Left Multiplier by  Left_M 
  Denote the Right Multiplier by  Right_M 
  Denote the Left Deniminator by  L_Deno 
  Denote the Right Multiplier by  R_Deno 

 Left_M = L.C.M / L_Deno = 1

 Right_M = L.C.M / R_Deno = x

Making Equivalent Fractions :

 5.3   Rewrite the two fractions into equivalent fractions

   L. Mult. • L. Num.      (10-3x)
   ——————————————————  =   ———————
         L.C.M               2x   

   R. Mult. • R. Num.      (11x-12) • x
   ——————————————————  =   ————————————
         L.C.M                  2x     

Adding fractions that have a common denominator :

 5.4   Adding up the two equivalent fractions 

 (10-3x) - ((11x-12) • x)     -11x2 + 9x + 10
 ————————————————————————  =  ———————————————
            2x                      2x       

Trying to factor by splitting the middle term

 5.5  Factoring  -11x2 + 9x + 10 

The first term is,  -11x2  its coefficient is  -11 .
The middle term is,  +9x  its coefficient is  .
The last term, "the constant", is  +10 

Step-1 : Multiply the coefficient of the first term by the constant   -11 • 10 = -110 

Step-2 : Find two factors of  -110  whose sum equals the coefficient of the middle term, which is   .

-110 + 1 = -109
-55 + 2 = -53
-22 + 5 = -17
-11 + 10 = -1
-10 + 11 = 1
-5 + 22 = 17
-2 + 55 = 53
-1 + 110 = 109


Observation : No two such factors can be found !! 
Conclusion : Trinomial can not be factored

Equation at the end of step  5  :

  -11x2 + 9x + 10
  ———————————————  = 0 
        2x       

Step  6  :

        -11x2+9x+10
Solve   ———————————  = 0 
            2x     

When a fraction equals zero :

 6.1   When a fraction equals zero ...

Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.

Here's how:

  -11x2+9x+10
  ——————————— • 2x = 0 • 2x
      2x     

Now, on the left hand side, the  2x  cancels out the denominator, while, on the right hand side, zero times anything is still zero.

The equation now takes the shape :
 -11x2+9x+10 = 0

Parabola, Finding the Vertex :

 6.2  Find the Vertex of y = -11x2+9x+10Parabolas have a highest or a lowest point called the Vertex . Our parabola opens down and accordingly has a highest point (AKA absolute maximum) .  We know this even before plotting  "y"  because the coefficient of the first term, -11 , is negative (smaller than zero). 
Each parabola has a vertical line of symmetry that passes through its vertex. Because of this symmetry, the line of symmetry would, for example, pass through the midpoint of the two  x -intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two real solutions. 
Parabolas can model many real life situations, such as the height above ground, of an object thrown upward, after some period of time. The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want to be able to find the coordinates of the vertex. 
For any parabola,Ax2+Bx+C,the  x -coordinate of the vertex is given by  -B/(2A) . In our case the  x  coordinate is   0.4091  
Plugging into the parabola formula   0.4091  for  x  we can calculate the  y -coordinate :  y = -11.0 * 0.41 * 0.41 + 9.0 * 0.41 + 10.0 or  y = 11.841

Parabola, Graphing Vertex and X-Intercepts :

 Root plot for :  y = -11x2+9x+10
 Axis of Symmetry (dashed)  {x}={ 0.41} 
 Vertex at  {x,y} = { 0.41,11.84}  
  x -Intercepts (Roots) :
 Root 1  at  {x,y} = { 1.45, 0.00} 
 Root 2  at  {x,y} = {-0.63, 0.00} 

  
 

Solve Quadratic Equation by Completing The Square

 6.3  Solving  -11x2+9x+10 = 0 by Completing The Square .
Multiply both sides of the equation by  (-1)  to obtain positive coefficient for the first term:
 11x2-9x-10 = 0 Divide both sides of the equation by  11  to have 1 as the coefficient of the first term :
  x2-(9/11)x-(10/11) = 0

Add  10/11  to both side of the equation : 
  x2-(9/11)x = 10/11

Now the clever bit: Take the coefficient of  x , which is  9/11 , divide by two, giving  9/22 , and finally square it giving  81/484 

Add  81/484  to both sides of the equation :
 On the right hand side we have :
  10/11 +  81/484 The common denominator of the two fractions is  484  Adding (440/484)+(81/484)  gives  521/484 
 So adding to both sides we finally get :
  x2-(9/11)x+(81/484) = 521/484

Adding  81/484  has completed the left hand side into a perfect square :
  x2-(9/11)x+(81/484)  =
  (x-(9/22)) • (x-(9/22)) =
 (x-(9/22))2 
Things which are equal to the same thing are also equal to one another. Since
  x2-(9/11)x+(81/484) = 521/484 and
  x2-(9/11)x+(81/484) = (x-(9/22))2 
then, according to the law of transitivity,
  (x-(9/22))2 = 521/484

We'll refer to this Equation as  Eq. #6.3.1  

The Square Root Principle says that When two things are equal, their square roots are equal.

Note that the square root of
  (x-(9/22))2   is
  (x-(9/22))2/2 =
 (x-(9/22))1 =
 x-(9/22)


Now, applying the Square Root Principle to  Eq. #6.3.1  we get:
  x-(9/22) = √ 521/484 

Add  9/22  to both sides to obtain:
  x = 9/22 + √ 521/484 

Since a square root has two values, one positive and the other negative
  x2 - (9/11)x - (10/11) = 0
 has two solutions:
 x = 9/22 + √ 521/484 
 or
 x = 9/22 - √ 521/484 

Note that  √ 521/484 can be written as
 √ 521  / √ 484  which is  521  / 22 

Solve Quadratic Equation using the Quadratic Formula

 6.4  Solving  -11x2+9x+10 = 0 by the Quadratic Formula .
According to the Quadratic Formula, x , the solution for  Ax2+Bx+C  = 0  , where  A, B  and  C  are numbers, often called coefficients, is given by :
 
 - B ±  √ B2-4AC
 x =  ————————
 2A  In our case, A = -11
 B =  9
 C =  10 Accordingly, B2 - 4AC =
 81 - (-440) =
 521Applying the quadratic formula :

 -9 ± √ 521 
 x = ——————
 -22  √ 521   , rounded to 4 decimal digits, is  22.8254 So now we are looking at:
  x = ( -9 ±  22.825 ) / -22

Two real solutions:

 x =(-9+√521)/-22=-0.628 

or:

 x =(-9-√521)/-22= 1.447 


Please let me know if you need any clarification. I'm always happy to answer your questions.
Jul 16th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jul 16th, 2015
...
Jul 16th, 2015
Aug 23rd, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer